Implementation and Analysis of Smart Helmet - G.A.Chougule,; Shubhada Sudhir Bhokare,; Shital Shivaji Mohite,; Sana Lajam Mujawar,; Pranali Laxaman Sasane, (Journal of Electronic Design Engineering, 2019)
Smart helmet is an innovative concept. In our work, there are mainly four features which are useful nowadays to prevent the accident and brain damage to the rider. It also detect the location of accident. There are so many reasons for causes of accident like not following the traffic rules, carelessness of driver as taking alcohol while driving. To avoid this, we have to implement a smart helmet; for that reason there are two important units. Helmet unit and bike unit, in helmet unit there is transmitter block and in bike unit a receiver block is there. The transmitter transmit signal from transmitter to receiver through RF transmitter. There is a limit switch to detect whether the rider is wearing the helmet or not. MQ2 sensor is used to detect whether the rider has taken alcohol or not while riding. GSM and GPS system is used to send the message to the relative whose sim number is inserted in GSM. GPS system is to detect the location of accident. These all features make simple helmet into smart helmet.